Kontribusi Teknologi Digital Terhadap Ketercapaian Pembelajaran Bahasa Indonesia Pada Siswa Kelas XI SMK Muhammadiyah Karanganyar - Wijayanto, Sendi; Setyarum, Ariesma (Universitas Negeri Padang, 2024)
This research aims to determine the contribution of digital technology to learning achievement in class XI students at SMK Muhammadiyah Karanganyar. The type of research used is quantitative research. The population in this study were all class XI students at SMK Muhammadiyah Karanganyar with samples from class XI Tabog and XI Tekfar. Data collection techniques use observation, interviews and questionnaires (questionnaires). The data analysis technique in this research is using the linearity test, Spearman rank correlation test and coefficient of determination test with the help of the SPSS application. The research results show that the linearity test produces a linear relationship between the two variables with a sig F value of 0.059>0.05. Based on the Spearman rank correlation test, a sign value of 0.00<0.05 was obtained with a correlation coefficient of 0.535, so that the relationship between digital technology and learning achievement has a correlation with a fairly strong level of relationship. The coefficient of determination in this research shows that digital technology contributes to learning achievement by 40.6%.Keywords: Digital technology, Achievement of Indonesian Language Learning